2D Stacks of MXene Ti3C2 and 1T‐Phase WS2 with Enhanced Capacitive Behavior. Issue 15 (6th August 2019) - Vyskočil, Jan; Mayorga‐Martinez, Carmen C.; Szőkölová, Kateřina; Dash, Apurv; Gonzalez‐Julian, Jesus; Sofer, Zdeněk; Pumera, Martin
Abstract: MXene‐based materials play an important role in the field of energy storage devices, owing to their layered structure with gravimetric/volumetric capacitances higher than that of graphene. However, owing to their tendency to bond to hydrogen or due to van der Walls forces, their performance is often reduced by the restacking of layers and subsequent reduction of their active surface area. In this work, we investigate the charge storage capacitance enhancement after inserting 1T‐phase WS2 nanospacers into the matrix of MXene Ti3 C2 through a simple sonication‐assisted procedure, forming a 2D stack structure. We demonstrated that each exfoliation step enhances the capacitive behavior when compared to the starting MAX phase (Ti3 AlC2 ). This new sandwich material shall have profound influence on the construction of 2D materials‐based supercapacitors. Abstract : MAX effect : Charge storage capacitance enhancement is investigated after inserting 1T‐phase WS2 nanospacers into the matrix of MXene Ti3 C2 through a simple sonication‐assisted procedure, forming a 2D stack structure. Each exfoliation step enhances the capacitive behavior when compared to the starting MAX phase (Ti3 AlC2 ). This new sandwich material shall have profound influence on the construction of 2D materials‐based supercapacitors.